Electroacupuncture Regulates Inguinal White Adipose Tissue Browning by Promoting Sirtuin-1-Dependent PPARγ Deacetylation and Mitochondrial Biogenesis - Tang, Qianqian; Lu, Mengjiang; Xu, Bin; Wang, Yaling; Lu, Shengfeng; Yu, Zhi; Jing, Xinyue; Yuan, Jinhong (Frontiers in Endocrinology, 2021)
Background: Previous studies had suggested that electroacupuncture (EA) can promote white adipose tissue (WAT) browning to counter obesity. But the mechanism was still not very clear. Aim: In this study, we aim to study the effect of EA on promoting inguinal WAT (iWAT) browning and its possible mechanism. Method: Three-week-old rats were randomly divided into a normal diet (ND) group and a high-fat diet (HFD) group. After 10 weeks, the HFD rats were grouped into HFD+EA group and HFD control group. Rats in the EA group were electro-acupunctured for 4 weeks on Tianshu (ST25) acupoint under gas anesthesia with isoflurane, while the rats in HFD group were under gas anesthesia only. Body weight and cumulative food intake were monitored, and H&E staining was performed to assess adipocyte area. The effect of EA on WAT was assessed by qPCR, immunoblotting, immunoprecipitation and Co-immunoprecipitation. Mitochondria were isolated from IWAT to observe the expression of mitochondrial transcription factor A (TFAM). Results: The Body weight, WAT/body weight ratio and cumulative food consumption obviously decreased (P < 0.05) in the EA group. The expressions of brown adipose tissue (BAT) markers were increased in the iWAT of EA rats. Nevertheless, the mRNA expressions of WAT genes were suppressed by 4-week EA treatment. Moreover, EA increased the protein expressions of SIRT-1, PPARγ, PGC-1α, UCP1 and PRDM16 which trigger the molecular conversion of iWAT browning. The decrease of PPARγ acetylation was also found in EA group, indicating EA could advance WAT-browning through SIRT-1 dependent PPARγ deacetylation pathway. Besides, we found that EA could activate AMPK to further regulate PGC-1α-TFAM-UCP1 pathway to induce mitochondrial biogenesis. Conclusion: In conclusion, EA can remodel WAT to BAT through inducing SIRT-1 dependent PPARγ deacetylation, and regulating PGC-1α-TFAM-UCP1 pathway to induce mitochondrial biogenesis. This may be one of the mechanisms by which EA affects weight loss.